Peningkatan Kepasitas Bidan Desa dalam Penanganan Kegawatdaruratan Maternal dan Neonatal di Wilayah Rawan Bencana - Elga Ceisaria Andani; Nurul Fathiyyah; Ainun Ganisia; Rakhmalia Imeldawati (Health Care : Journal of Community Service, 2025)
Disaster-prone areas face major challenges in maternal and neonatal emergency care, particularly when referral access, electricity, communication, and health facilities are disrupted. Village midwives, as frontline health workers, need adequate capacity to recognize, stabilize, and refer maternal and neonatal emergency cases promptly. This community service activity aimed to improve the knowledge, attitudes, and skills of village midwives in managing maternal and neonatal emergencies in disaster-prone areas. The method was conducted through a hybrid disaster preparedness training module consisting of education, learning videos, waterproof portable handbooks, standard operating procedure posters, field simulations, and strengthening of referral communication networks. Evaluation was carried out using pre-tests, post-tests, skill observation, and emergency response time recording during simulations. The results showed an increase in midwives’ knowledge from 42.5% to 79.3% with p<0.001. Proactive attitude scores increased from 3.0 to 4.5, while practical skills reached 88% success. Strengthening the WhatsApp-based referral network reduced simulation response time by up to 52%. Hybrid disaster preparedness training modules were proven effective in improving village midwives’ capacity and strengthening maternal-neonatal service preparedness in disaster-prone areas.